PENGARUH STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL PADA PERUSAHAAN JAKARTA ISLAMIC INDEX (JII) YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015 – 2017 - ATIKA RAHMI; LILI FADLI MUHAMMAD; FITRI ANA (BALANCING: Accountancy Journal, 2021)
The population used in this study is companies included in the Jakarta Islamic Index (JII) listed on the Indonesia Stock Exchange for the period 2015-2017. The method used in sample collection is a purposive sampling method with 45 observations. This study uses secondary data obtained from the JII Company Financial Statements using simple linear regression analysis techniques. The results showed that the structure of assets affect the capital structure of JII companies listed on the Indonesia Stock Exchange in 2015 - 2017, this is based on the results of the t test which shows the value of t arithmetic (-2.952) t table (- 2.01669) and has a significance value of 0.005 0.05 so it can be concluded that the structure of assets affects the capital structure ( accepted).